Prevalence of Persistent Post-Concussion Syndrome in Adults After Mild Traumatic Brain Injury - Putra Agina Widyaswara Suwaryo; Fairrul Kadir; Azizan Omar; Sukhbeer Kaur Darsin Singh (Nurse Media: Journal of Nursing)
Background: Although mild Traumatic Brain Injury (mTBI) is one of the primary causes of death and disability worldwide, research on the prevalence of post-concussion syndrome (PCS) after mTBI is still extremely limited. Previous studies have shown that approximately 10-15% of mTBI patients experience PCS, yet these studies often have different methodologies and sample sizes.